Perspectives on health examination for asylum seekers in relation to health literacy - focus group discussions with Arabic and Somali speaking participants - Josefin Wångdahl; Ragnar Westerling; Per Lytsy; Lena Mårtensson (BMC, 2019)
Abstract Background Asylum seekers coming to most countries are offered a specific health examination. A previous study concluded that a considerable proportion of those taking part of it in Sweden had poor experiences of the communication in and the usefulness of this examination and had poor health literacy. The aim of this study was to explore in greater depth the experiences of the health examination for asylum seekers among Arabic- and Somali-speaking participants in Sweden. A secondary aim was to examine experiences and discuss findings using a health literacy framework. Methods Seven focus group discussions were conducted with 28 Arabic and Somali speaking men and women that participated in a health examination for asylum seekers. Data were analyzed by latent content analysis. Results One overarching theme - beneficial and detrimental - was found to represent the participants' experiences of the health examination for asylum seekers. Three categories were identified that deal with those experiences. The category of "gives some good" describes the examination as something that "gives support and relief" and "cares on a personal level." The category of "causes feelings of insecurity" describes the examination as something that "lacks clarity" and that "does not give protection." The category "causes feelings of disappointment" views the examination as something that "does not fulfil the image of a health examination" and "does not focus on the individual level." Conclusion The health examination for asylum seekers was experienced as beneficial and detrimental at the same time. The feelings were influenced by the experiences of information and communication before, during and after the examination and on how health literate the organizations providing the HEA are. To achieve more satisfied participants, it is crucial that all organizations providing the HEA become health literate and person-centered.